Anti-inflammatory profile of Aegle marmelos (L) Correa (Bilva) with special reference to young roots grown in different parts of India - Azad Rajaram; G.R. Vanaja; Preeti Vyakaranam; Aparna Rachamallu; Gorla V. Reddy; Kotha Anilkumar; Kalle M. Arunasree; Anurag Dhyani; Narapureddy Krishna Prasad; Sakshee Sharma; Mahesh Chandra Joshi; Gaya Prasad Kimothi; et al. (Journal of Ayurveda and Integrative Medicine, 2018)
Background: Aegle marmelos (Bilva) is being used in Ayurveda for the treatment of several inflammatory disorders. The plant is a member of a fixed dose combination of Dashamoola in Ayurveda. However, the usage of roots/root bark or stems is associated with sustainability concerns. Objectives: The present study is aimed to compare the anti-inflammatory properties of different extracts of young roots (year wise) and mature parts of Bilva plants collected from different geographical locations in India, so as to identify a sustainable source for Ayurvedic formulation. Materials and methods: A total of 191 extracts (petroleum ether, ethyl acetate, ethanol and aqueous) of roots, stems and leaves of A. marmelos (collected from Gujarat, Maharashtra, Odisha, Chhattisgarh, Karnataka and Andhra Pradesh region) were tested for anti-inflammatory effects in vitro on isolated target enzymes cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LOX), lymphocyte proliferation assay (LPA), cytokine profiling in LPS induced mouse macrophage (RAW 264.7) cell line and in vivo carrageenan induced paw edema in mice. Results: Of 191 extracts, 44 extracts showed COX-2 inhibition and 38 extracts showed COX-1 inhibition, while none showed 5-LOX inhibition. Cytokine analysis of the 44 extracts showing inhibition of COX-2 suggested that only 17 extracts modulated the cytokines by increasing the anti-inflammatory cytokine IL-2 and reducing the pro-inflammatory cytokines like IL-1β, MIP1-α and IL-6. The young (2 and 3 years) roots of Bilva plants from Gujarat and young (1 yr) roots from Odisha showed the most potent anti-inflammatory activity by suppressing the pro-inflammatory cytokines and inducing anti-inflammatory cytokines. These three extracts have also shown in vivo anti-inflammatory activity comparable to that in adult stem and root barks. Conclusion: The present study reveals that young roots of Bilva plants from Gujarat and Odisha region could form a sustainable source for use in Ayurvedic formulations with anti-inflammatory activities. The present study also indicates that the region in which the plants are grown and the age of the plants play an important role in exhibiting the anti-inflammatory effect. Keywords: Aegle marmelos, Inflammation, Ayurveda, Cyclooxygenase-1 & 2, 5-Lipoxygenase, Immunomodulation